Avaliação do reagente de Fenton e Foto-Fenton na remoção de matéria orgânica e toxicidade em um efluente hospitalar - Larissa Marques Diniz (2015)
The hospital sewage originates in various activities present in a hospital, such as: kitchen, laundry system, heating and cooling systems, laboratories, radiology departments, outpatient departments, transfusion centers and nurseries. Therefore, it is a variable effluent from the point of view of physico-chemical characterization and flow. The main contaminants are persistent chemicals and a complex mixture of organic matter, detergent, surfactant, antiseptic, solvent and drugs. It also has in its composition bacteria that can interfere with the natural ecosystem by modifying the arrangement of bacterial communities. In Brazil there is a tendency to classify these as a domestic wastewater effluent, resulting in a set treatment. However, the hospital sewage has a high toxicity, 5 to 15 times higher than domestic sewage and therefore, the conventional biological treatment ceases to be an attractive method. Therefore, new technologies are being investigated with the objective of further removal of pollutants, before the release of the receiving body. In this context it stands out the Advanced Oxidation Processes. The present study aims to evaluate the Fenton reagent and Photo- Fenton in removing organic load and toxicity of the Hospital das Clínicas effluent (Belo Horizonte, Minas Gerais, Brazil). The actual effluent studied presents a high organic load and a high concentration of suspended solids. You can also see a wide variation in the physicochemical characterization and flow of it. Secondary data characterizing the hospital sewage were investigated from October 2013 to April 2014, and after this step left to the acquisition of primary data. There were 5 sampling campaigns, it was composed totaling 7 hours of collection. Two collection points were investigated: Point 1, referring to the sample 1, which includes the wastewater generated in the sterile laundry and Material Center and Point 2, concerning the effluent generated in the North Wing, South, East and West of the hospital. After this stage it was decided to merge the samples 1 and 2, thus generating the sample 3, effluent which was passed through the steps of planning experiments and treatment. According to the design of experiments made by Minitab software, the best dosage H2O2 and Fe2 was respectively 1,000 mg / L and 500 mg / L. The next step was then to treat the effluent via Fenton and Photo-Fenton. Fenton reagent was capable of removing 85% of the COD and 55% of the TOC and the photo-Fenton 90.7% of the COD and 77.9% of the TOC. In order to investigate the quality of the effluent. the samples 1, 2 and 3 was passed the in test of acute toxicity with the marine bacterium Alivibrio fischeri. It was observed that samples 1 and 3 were given as a non-toxic and 2 showed toxicity. The treated effluent via Fenton, although it was not accused toxicity, was detected hormesis and in effluent after photo-Fenton was detected toxicity. Thus, the treatments were effective in removing organic load, however, there is the need for monitoring of chronic toxicity in order to assess the real impact of polluting effluent.